Biogenic fenton-like reaction involvement in aerobic degradation of C60 by Labrys sp. WJW. (1st March 2021) - Wang, Jingwei; Ma, Qiao; Zhang, Zhaojing; Diko, Catherine Sekyerebea; Qu, Yuanyuan
Abstract: Buckminster fullerene (C60 ), the most representative type among fullerenes, has attracted widely attentions because of its many potential applications. The increasing application of fullerene and limited knowledge of its environmental fate are required concerns. Herein, the biotransformation of C60 by Labrys sp. WJW was investigated. Cell numbers reached 25.76 ± 1.85 folds within 8 days using 100 mg/L C60 as sole carbon source. The biotransformation of C60 by Labrys sp. WJW was analyzed by various characterization methods. Raman spectra indicated that strain WJW broke the soccer ball like structure of C60 . After 12 days, over 60% of C60 was degraded evidenced by UV–vis spectrophotometry and liquid chromatography-mass spectrometry. The underlying biotransformation mechanism of C60 through an extracellular Fenton-like reaction was illustrated. In this reaction, the OH production was mediated by reduction of H2 O2 involving a continuous cycle of Fe(II)/Fe(III). Bacterial transformation of C60 will provide new insights into the understanding of C60 bioremediation process. Graphical abstract: Image 1 Highlights: Aerobic biotransformation of fullerene (C60 ) by bacterium. Labrys sp. WJW could degrade and uptake carbon from C60 to support growth. Biotransformation through an extracellular Fenton-like reaction.